Neuroendoscopy surgery for hypertensive intracerebral hemorrhage with concurrent brain herniation: a retrospective study of comparison with craniotomy - Zhan, Yuan; Zou, Xiaojun; Wu, Jiebin; Fu, Liang; Huang, Wei; Lin, Junming; Luo, Fei; Wang, Wenhao (Frontiers in Neurology, 2023)
Background Hypertensive intracerebral hemorrhage combined with cerebral hernia (HIH-CH) is a serious condition. Neuroendoscopy can effectively remove intracranial hematoma, but there is no relevant research support for its utility in patients with HIH-CH. The purpose of this study is to investigate the efficacy and safety of neuroendoscopy in patients with HIH-CH. Methods Patients with HIH-CH who received craniotomy or neuroendoscopy treatment were included. The patients were divided into craniotomy (CHE) group and neuroendoscopy (NEHE) group. Clinical data and follow-up outcome of the two groups were collected. The primary outcome was hematoma clearance. Results The hematoma clearance rate (%) of patients in NEHE group was 97.65 (92.75, 100.00), and that of patients in CHE group was 95.00 (90.00, 100.00), p > 0.05. The operation time and intraoperative bleeding volume of patients in NEHE group were significantly less than those in CHE group (p < 0.05). There was no significant difference in the volume of residual hematoma and the incidence of rebleeding between the two groups (p > 0.05). The length of stay in ICU in NEHE group was significantly shorter than that in CHE group (p < 0.05). Conclusion Neuroendoscopy can safely and effectively remove the intracranial hematoma in patients with hypertensive intracerebral hemorrhage and cerebral hernia, significantly shorten the operation time, reduce the amount of intraoperative hemorrhage, shorten the ICU stay.